Kreativitás és valóság a gazdálkodás eredményének meghatározásában - Wickert, Irén; Szarvas-Fekete, Tibor; Ágoston, Anita (Acta Scientiarum Socialium, 2019)
The determining of the outcome periodically is primary important in the operation of businesses. The assets and their changes, as well as the profit generating efficiency, ensure that the business continues to operate. In Hungary the Act C of 2000 on Accounting defines the method of accounting for economic events; however, the practice the accounting, which is based on experience, can make a move towards the creativity. The principle, which is not forbidden by the law, that is "free". The interpretation and recording of economic events and the judgement of their impact on outcome can often be based on subjective assessment. This article deals with the effects of subjective judgment and choosing on the results.
Keywords: accounting; result; practice; creativity